Novel functionalized electrospun nanofibrous adsorbent from chitosan/poly(glycidyl methacrylate) blends for boron removal - Nadiah Khairul Zaman, 1987- , author; Mohamed Mahmoud El-Sayed Nasef; Kamaruddin Hashim; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2014